Developing Aviation Smart Campus Through Digital Transformation Strategy: Case Study at Indonesia Aviation Polytechnic - Dian Anggraini Purwaningtyas; Iwan Ardiansyah Ardiansyah; Wahyu Widayati Widayati (Journal of Innovation in Educational and Cultural Research, 2022)
The application of digital technology to business processes brings a new atmosphere in the era of technological disruption. The increasing number of transportation users makes all air transportation industry operators compete to provide services and facilities without neglecting safety. Personnel working in the aviation sector are keys to successful service delivery. Good quality education begins with the management of the aviation campus. The application of ICT or digital technology in aviation schools in the digital transformation era will bring a fresher atmosphere and innovation. This paper aims to make the concept of digital transformation on aviation campuses based on business processes. Based on the dimensions of digital transformation, which consists of 9 aspects, as well as the value chains of the five porters, a matrix for the concept of digital transformation for aviation campuses can be created. By paying attention to customer experience, processes and business models that make it possible to create new businesses; the implementation of Digital Transformation can be achieved. A simple concept of IT Architecture, this paper can provide a plan for making a smart aviation campus